Single event multilevel surgery in spastic patient : a Hospital Tengku Ampuan Afzan (HTAA) experience - Nik Abdul Adel, Nik Alyani; Abdul Razak, Ardilla Hanim; Awang, Mohd Shukrimi; Loh, LL (2020)
INTRODUCTION: